Unlocking Technological Capabilities to Boost the Performance of Accounting Firms - Helmi Hentati; Neila Boulila Taktak (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- What is the impact of the use of Internet technology on the financial and non-financial performance of accounting firms? Motivation- The evaluation of the performance of an accounting firm is based on the technological factor. This study is based on a multi-activity study of accounting firms which includes mainly reporting, auditing, and tax activities to create a realistic approach to appropriately measure the performance of accounting firms. Especially with the scarcity of studies have been conducted regarding the organizational impact of technologies on accounting firms. Idea- the purpose of the study was to determine the effect of technology on the performance of accounting firms, based on empirical data. Data- 104 observations were received via a questionnaire sent to the heads of the accounting firms. Tools- we used linear regression to measure the impact of technology use on performance and validated our results graphically. Findings- the results demonstrate that accounting firms equipped with technological capabilities benefit from superior performance. Contribution- these results have practical implications, suggesting that there is value in fostering a mutually beneficial relationship between academic research and the professional practice of accounting firms. Accounting professionals can utilize research insights to enhance their working methods, policies, and decision-making processes pertaining to technology. This collaboration can lead to tangible improvements within the accounting field and contribute to its ongoing development.
Keywords: M49; 650; Technology Use; Accounting Firms; Organizational performance; Organizational innovation